Comparison of the effects of carbisocaine and other local anesthetics on 32P incorporation into individual and total phospholipids in synaptosomes - Horáková, L; Stolc, S (General physiology and biophysics, 1988)
The aim of the paper was to study the effect of carbisocaine, a new local anesthetic with high liposolubility on incorporation of 32P into individual and total phospholipids and to compare its effect with that of other local anesthetics (procaine, lidocaine, cinchocaine, heptacaine). Carbisocaine decreased 32P incorporation into neutral phospholipids and increased the incorporation into acid phospholipids, presumably by inhibiting phosphatidate phosphohydrolase, similarly as reported for other anesthetics (Brindley and Bowley 1975). The increased incorporation of 32P into phosphatidylserine induced by carbisocaine suggests that this phospholipid is also synthetised from phosphatidic acid. At low concentrations, the local anesthetics studies were found to increase 32P incorporation into total phospholipids, whereas at high concentrations they reduced 32P incorporation. This biphasic effect is in agreement with the incorporation of 14C from glucose into lipids (Lassánová et al. 1984) and with the effect of cinchocaine on glycerol incorporation into phospholipids (Allan and Michell 1975), suggesting that local anesthetics affect de novo synthesis of phosphatidic acid. Carbisocaine increased 32P incorporation into phospholipids, in concentrations lower by several orders of magnitude as compared to the other local anesthetics studied. A rough correlation was observed between the concentrations at which the local anesthetics showed stimulatory effect on 32P incorporation, and the average effective concentrations of the respective anesthetics. No such correlation could be found for carbisocaine.
Keywords: kinetika; synaptozomy; Rats; Carbamates; mozek; krysa rodu Rattus; karbamáty; Brain; Synaptosomes; zvířata; Anesthetics, Local; Phospholipids; Kinetics; Phosphates; radioizotopy fosforu; fosfáty; anestetika lokální; fosfolipidy; Phosphorus Radioisotopes; Animals